2006
DOI: 10.1068/b31123
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Layout and Face-to-Face Interaction in Offices—A Study of the Mechanisms of Spatial Effects on Face-to-Face Interaction

Abstract: This paper reports a study that uses space syntax theories and techniques to develop a model explaining how spatial layouts, through their effects on movement and visible co-presence, may affect face-to-face interaction in offices. While several previous space syntax studies have shown that spatial layouts have significant effects on movement and face-to-face interaction in offices, none has investigated the relations among movement, visible co-presence, and face-to-face interaction in offices with significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
115
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(120 citation statements)
references
References 26 publications
4
115
1
Order By: Relevance
“…The frequency of meetings between people who work on different floors inside a building is lower than between people on the same floor (Parsons, 1976in: Rashid et al, 2006Spiliopoulou and Penn, 1999). This effect becomes smaller when the floors are bigger (Grajewski, 1992;Becker et al, 1995).…”
Section: Position In the Buildingmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of meetings between people who work on different floors inside a building is lower than between people on the same floor (Parsons, 1976in: Rashid et al, 2006Spiliopoulou and Penn, 1999). This effect becomes smaller when the floors are bigger (Grajewski, 1992;Becker et al, 1995).…”
Section: Position In the Buildingmentioning
confidence: 99%
“…Working in the same project room provides accessibility, but also normal workspaces that are visually open enhance face-to-face interaction through seeing and overhearing (Ward and Holtham, 2000;Rashid et al, 2006;Markhede and Koch, 2007;Sailer et al, 2007).…”
Section: Co-presencementioning
confidence: 99%
“…The physical environment of workplaces, which include the physical design as well as the ambient environment of workplaces, is no different. Workplace design is particularly important for it also facilitates and/or constrains individual, group and organizational psychology, behaviors, functions and performance to define the organizational and professional environments in the workplace (for evidence supporting the claim, in addition to the above citations also see Appel-Meulenbroek & Feijts, 2007;de Croon et al, 2005;Haynes, 2007;Lee & Brand, 2005;Niemi &Lindholm, 2010;Rashid, et al, 2006Rashid, et al, , 2009. For example, in a review of literature in fields relevant to Corporate Real Estate (CRE), Appel-Meulenbroek and Feijts (2007) found that as many as 51 aspects of the physical environment of CRE could affect organizational performance.…”
Section: Introductionmentioning
confidence: 99%
“…In these workplaces, spaces are also made highly interconnected with increased visibility, openness, and accessibility in order to boost chance encounters which can lead to meaningful interactions. Additionally, these workplaces also provide a wide variety of features, such as kitchens, stocked refrigerators, central service hubs, recreational facilities, comfortable furniture, and attractive lounge-like spaces in public and/or semipublic territories (Rashid et al, 2006;2009). A recent publication of the Office of the Government-wide Policy of the General Services Administration of the US Government includes several examples of such innovative offices (OGP, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Wineman and Peponis (2010) analyzed the movement and syntax of an open plan museum. Rashid (2006) performed axial analysis of space syntax in four different workplaces and found the relation between communication and office layouts. Peponis et al (2007) analyzed the space syntax of work places and the spatial structure supporting organizational cultures using cognitive functions.…”
Section: Introductionmentioning
confidence: 99%